A Spatial Reflection of Social Transformation: Taksim Municipal Gazino, 1939 - Begüm Sena Önal Özmalatyalılar; Meltem Ö. Gürel (Art-Sanat)
Taksim Municipal Gazino, which hosted its visitors inside the İnönü Promenade between 1939 and 1967, was one of the leading examples of gazinos (an entertainment venue) built with the support of the state in the early republican era in Turkey. Designed by the municipality architect, Rüknettin Güney, within the scope of French city planner Henri Prost’s İstanbul Master Plan, the edifice was a quintessential example of modern architecture that epitomized the state’s Westernization ideology. This article examines the gazino practice as a spatial reflection of social transformation by presenting a historical and spatial reading of the Taksim Municipal Gazino. The study analyzes the gazino structure as a power mechanism that produces secular identities by focusing on the dialectic between the spaces in the building and the experiences of its patrons. The analysis of architectural drawings, photographs, and literary works associated with the building, on the one hand, reveals how the architect, operating as a cultural leader, utilized architectural creation to present the Western lifestyle to society. On the other hand, it indicates that Taksim Municipal Gazino served as a platform for individuals to display their modernity. Moreover, the study propounds that the building contributed to the modernization process of the newly established nation-state, and it has served as a spatial tool that notably strengthened the position of female regulars in the public sphere.